La transformación digital y su aporte en los procesos de gestión empresarial - Carbajo Lara, Betty Yuliana (2024)
We have heard nowadays a lot about the concept of digital transformation; however, not everyone is clear about its meaning and applicability. This paper seeks to expand the concepts of digital transformation and how they currently contribute to the improvement of business management processes. Talking about digital transformation does not only imply referring to technology, but also encompasses a change in organizational culture, which is one of its main challenges. To help the reader understand the context, the paper describes the case of ALFA S.A.C. where applied research with a non-experimental design has been carried out. The study consisted in interviewing 35 employees at ALFA S.A.C., and evaluating the areas and processes of the entire organization. The research included the analysis of the micro and macro environment of the company through the SWOT matrix and Porter’s five forces. The results showed the need to make changes in the business management of ALFA S.A.C. through the implementation of operational processes in new technological trends, as well as a change in the employees’ mindset.